The Mix Project / Madiana Norhadi ... [et al.] - Norhadi, Madiana; Noor Azmi, Farah Wahida; Kamaruzaman, Nuraida Syafina; Ashari, Mohamad Asyreeq; Romayli, Mohammad Haziq (2021)
The Mix Project was founded on beginning of this year and located in Dengkil Selangor. It was created by Puan Azra Rahman which is 30 years old and graduated in architecture from University Technology Malaysia Sri Iskandar. The Mix Project is a business that specializes in selling fudgy brownies pre-mix. The Mix Project also has four people who work at their company which is Puan Azra as the manager and owner, her beloved husband as an operations manager and two members as the production team. Essentially, The Mix Project was launched after the owner made some studies on independent cake firms and she founded that it was valuable to start the business regarding on what she has studies. She also has the goal of eventually entering the worldwide market. Since they were selling the most competitive product, their product is designed with the goal of attempting to provide an easy way to make a fudgy brownie without fail as the brownies itself has premium ingredients which consist of imported chocolate and cocoa powder. Finally, this report also includes an introduction, background of the study, company information, company analysis, finding and discussion as well as conclusion.